Comparative physiology of Australian quolls (Dasyurus; Marsupialia) - Cooper, Christine; Withers, P. (2010)
Quolls (Dasyurus) are medium-sized carnivorous dasyurid marsupials. Tiger (3,840 g) and eastern quolls (780 g) are mesic zone species, northern quolls (516 g) are tropical zone, and chuditch (1,385 g) were once widespread through the Australian arid zone. We found that standard physiological variables of these quolls are consistent with allometric expectations for marsupials. Nevertheless, inter-specific patterns amongst the quolls are consistent with their different environments. The lower T ^sub b^ of northern quolls (34°C) may provide scope for adaptive hyperthermia in the tropics, and they use torpor for energy/water conservation, whereas the larger mesic species (eastern and tiger quolls) do not appear to. Thermolability varied from little in eastern (0.035°C °C^sup -1^) and tiger quolls (0.051°C ºC^sup -1^) to substantial in northern quolls (0.100°C ºC^sup -1^) and chuditch (0.146°C ºC^sup -1^), reflecting body mass and environment. Basal metabolic rate was higher for eastern quolls (0.662 ± 0.033 ml O^sub 2^ g^sup -1^ h^sup -1^), presumably reflecting their naturally cool environment. Respiratory ventilation closely matched metabolic demand, except at high ambient temperatures where quolls hyperventilated to facilitate evaporative heat loss; tiger and eastern quolls also salivated. A higher evaporative water loss for eastern quolls (1.43 ± 0.212 mg H^sub 2^O g^sup -1^ h^sup -1^) presumably reflects their more mesic distribution. The point of relative water economy was low for tiger (-1.3°C), eastern (-12.5°C) and northern (+3.3) quolls, and highest for the chuditch (+22.6°C). We suggest that these differences in water economy reflect lower expired air temperatures and hence lower respiratory evaporative water loss for the arid-zone chuditch relative to tropical and mesic quolls.